A Sheet of Paper Salved From Fire. Post-Laussanne Lyric of Adam Mickiewicz "Drzewo" ("A Tree") and "Wsłuchać się w szum wód głuchy..." ("To Listen to the Dull Sough of Waters...") - Szczeglacka-Pawłowska, Ewa (Colloquia Litteraria, 2018)
The article is an interpretation study of two lyric poems by Adam Mickiewicz (Drzewo and [Wsłuchać się w szum wód głuchy...], 1842). It grows out of an analysis of a lost manuscript and the history of the above-mentioned poems’ editions (including commentaries), as well as the notebook romanticism [romantyzm brulionowy] concept developed by the author. This concept encapsulates the inedita and creates a separate sphere in the epoch’s literary art and aesthetics.